PSVII-7 Relationship of slice shear force and quality grade of strip loin steaks from Brangus steers. (7th December 2018) - Hamblen, H; Flowers, S; Leal Gutierrez, J; Rodriguez, E; Carr, C; Scheffler, T; Scheffler, J; Mateescu, R
Abstract: The quality grade system used in the United States to identify carcasses with superior eating satisfaction to consumers is based on the amount of intramuscular fat (marbling) within the ribeye and the maturity of the carcass. However, the most important quality attribute for consumers is tenderness. The objective of this study was to investigate the relationship between quality grade and tenderness assessed by slice shear force in strip loin steaks from Brangus cattle. Brangus steers (n = 860) were harvested when they reached approximately 1.27 cm fat over the ribeye. Hot carcass weight (HCW), dressing percentage (DP), marbling score (MARB; 100 to 199 = practically devoid, 200 to 299 = traces, 300 to 399=slight, 400 to 499=small, 500 to 599=modest, 600 to 699=moderate, 700 to 799=slightly abundant, 800 to 899=moderately abundant, and 900 to 999=abundant), ribeye area (REA), fat over the eye (FOE), and kidney pelvic and heart fat percentage (KPH) were evaluated for each animal. Quality grades and yield grades were calculated according to industry standards. A steak from the longissimus lumborum muscle was collected from each carcass, aged for 14 d and used for slice shear force testing to determine the tenderness. Data was analyzed with a general linear model with cooking loss, ranch, and feedlot as fixed effects. The quality grades ranged from high standard to average prime and the average of slice shear force values was 26.09 ± 8.76 kg. Quality grade had a significant effect on Slice Shear Force values (P = 0.0078), showing that quality grade significantly impacts tenderness. However, there was a high level of variation in Slice Shear Force values within quality grades. This indicates that carcasses with high quality grades could have meat with unacceptable tenderness, which could affect the demand for beef products.